NATURAL FOOD OF CHANNA PUNCTATA (BLOCH) FROM KANGRA, HIMACHAL PRADESH - KOUNDAL, ARUN; DHANZE, RANI (Journal of the Inland Fisheries Society of India, 2021)
Analysis of gut content is widely used to ascertain the food and feeding habits of fishes. Accurate description of diets and feeding habits providesthe basis for understanding the trophic interactions in aquatic food webs (Vander et al. 2000). Feeding is usually a part of the daily routine, the rate of which sometimes changes with the breeding activities of the fish. The nature of food composition of fish also reveals possible habitats in which it lives. In Himachal Pradesh, most cultivable fish species includes carps and trouts, mostly require good amount of water (qualitatively and quantitatively) but C. punctata which is well known for its hardy nature, can survive well in harsh environmental conditions (low water levels, low dissolved oxygen, unclear-swampy water regions, etc.). Moreover it’s capability of engulfing oxygen from air, good survivability and growth at higher densities, nutritive and medicinal qualities and above all less chances of disease makes it best option for culture practice (Alam and Parween, 2001), Dambo and Rana (1992), Munshi and Hughes (1992) Ghosh (2006), Kumar (1992), Kuppulakshmi et al. (2008), Le and Ng (1991). Hence correct knowledge of the relationship of fish with its food organism is essential for the production and exploitation of fish stocks. Different workers like Prasad et al. (1987), Rao et al. (1998), Dasgupta (2000), Saxena (2000), Nazrul et al. (2004) and Bhuiyan et al. (2006), have studied the food and feeding behaviours of this species, while several other workers like Guseva (1990), Arul (1991), Ahmed (1993), Mohantyand Samataray (1996), Jinguang and Fast (1996), Congxin et al. (1997) and Chaudhary and Biswas (2004), have done the same work in differentspecies of Genus Channa. Considering the importance of this species the present study has been conducted.